2021
DOI: 10.3390/en14092673
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Performance of Hydropower Dams Supported by the World Bank Group, 1975–2015

Abstract: This paper assesses the economic benefits of 57 World Bank Group-sponsored hydropower dam plant investments. Hydropower dams are among the main sources for producing electricity and the largest renewable source for power generation throughout the world. Hydropower dams are often a lower-cost option for power generation in Clean Energy Transition for addressing global climate change. Despite its conspicuous aspects, constructing hydropower dams has been controversial. Considering the World Bank’s long history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…A recent survey on 57 World Bank Group-sponsored hydropower dam plant investments showed that dams produced a present net value of over half a trillion USD by 2016. The evaluated hydropower portfolio reduced over a billion tons of CO 2 that amounted to nearly USD 350 billion when taking the global environmental benefit into account [24]. Hence, hydro dams usually contribute to no poverty but assessing their impact on mitigating climate change needs multi-aspect models consisting of various media [25].…”
Section: Hydro Projects and Sustainable Developmentmentioning
confidence: 99%
“…A recent survey on 57 World Bank Group-sponsored hydropower dam plant investments showed that dams produced a present net value of over half a trillion USD by 2016. The evaluated hydropower portfolio reduced over a billion tons of CO 2 that amounted to nearly USD 350 billion when taking the global environmental benefit into account [24]. Hence, hydro dams usually contribute to no poverty but assessing their impact on mitigating climate change needs multi-aspect models consisting of various media [25].…”
Section: Hydro Projects and Sustainable Developmentmentioning
confidence: 99%
“…The estimated nominal costs are extracted from the Staff Appraisal Reports (SARs) and Implementation and Completion Reports (ICRs) made available by the World Bank for each of the projects. Following Bacon and Besant-Jones (1998), Awojobi and Jenkins (2015), and Baurzhan et al (2021), the estimated real cost is taken as the difference between the estimated nominal cost and the amount set aside as price contingency. The actual nominal costs are extracted from the ICRs of the World Bank, while the actual real costs are the deflated actual nominal costs.…”
Section: Datamentioning
confidence: 99%
“…The total actual real cost is computed as follows: where is the actual nominal cost, FCX is the foreign component, is the foreign price index, and is the domestic price index. Finally, cost overrun is computed as the ratio of actual real costs to the estimated real cost. The benefits of the hydropower projects are calculated as the value of the avoided generation costs of fossil fuel-powered plants that would be required to be built and operated to supply the same volume of electricity as would be supplied by the hydro dam (Zuker & Jenkins, 1984; Baurzhan et al, 2021; Jenkins et al, 2022). These avoided costs were estimated based on the exact technologies and their degree of displacement specified by the World Bank at the time of appraisal.…”
Section: Datamentioning
confidence: 99%
“…For example, most of the nuclear power plants used in this study were constructed during the 1970s. A subsequent study examined hydroelectric power plants and their time overruns by considering 57 hydroelectric dams installed between 1975 and 2015 [28]. This study only included hydroelectric facilities financed by the World Bank Group and assessed the uncertainties in the costs and benefits of the technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study only included hydroelectric facilities financed by the World Bank Group and assessed the uncertainties in the costs and benefits of the technology. The data analyzed indicated that 80% of the 57 facilities considered experienced a time overrun, which highlights the need to accurately predict the construction of hydroelectic facilities [28].…”
Section: Literature Reviewmentioning
confidence: 99%